2003
DOI: 10.1002/mame.200300151
|View full text |Cite
|
Sign up to set email alerts
|

Transcrystallinity in Surface Modified Aramid Fiber Reinforced Nylon 66 Composites

Abstract: Aramid (kevlar‐49) fibers were surface treated by two different methods to induce roughness and then used to produce unidirectional nylon 66 based composites. The transcrystallinity generated around the treated fibers was characterized by SEM and polarized light microscopy and compared with the regular transcrystalline layers produced by pristine aramid under the same processing conditions. The treated fibers generated a double transcrystalline layer, the inner layer being thinner and more compact than the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 17 publications
0
10
0
2
Order By: Relevance
“…This structure begins to develop on the walls of CNT before the most common supermolecular structure of spheroulites (T c,1 peak), which is observed thereupon during the cooling. The trans-crystallinity structure has been reported in various conventional polymer/fiber composites [38,39] and recently in nanocomposites. In particular, in Refs.…”
Section: Effects Of Mwcnt Addition On the Thermal Transitions Of Ippmentioning
confidence: 92%
“…This structure begins to develop on the walls of CNT before the most common supermolecular structure of spheroulites (T c,1 peak), which is observed thereupon during the cooling. The trans-crystallinity structure has been reported in various conventional polymer/fiber composites [38,39] and recently in nanocomposites. In particular, in Refs.…”
Section: Effects Of Mwcnt Addition On the Thermal Transitions Of Ippmentioning
confidence: 92%
“…A number of studies indicated that many of the thermoplastic composites based on semicrystalline polymeric matrices were observed to present some transcrystalline layers on the fiber surfaces due to the fact that the reinforcing fibers act as giant nucleation sites enhancing the nucleation and crystallization rates of polymeric matrices. 59 61 Considering of a high nucleating ability of long PI fiber for the crystallization of PA6 matrix, the formation of transcrystalline layers is anticipated within the PA6/PI fiber composites. An observation of polarizing optical microscopy was performed to investigate the transcrystallinity of PA6/PI fiber composites.…”
Section: Resultsmentioning
confidence: 99%
“…Feldman [11] treated Kevlar 49 fiber surface with saturated aqueous bromine solution for 15 s then treated with 25% NH3 solution for 30 s. Scanning electron microscope images illustrated etched formation on fiber surface which tend to increase fiber surface roughness. Results show decrease in tensile strength and Young modulus in comparison with untreated Kevlar fiber reinforced composite.…”
Section: Introductionmentioning
confidence: 99%